Exposure of the Basophilic Cell Line KU812 to Liposomes Reveals Activation Profiles Associated with Potential Anaphylactic Responses Linked to Physico-Chemical Characteristics - Alexander J. Plant-Hately; Burcu Eryilmaz; Christopher A. W. David; Danielle E. Brain; Bethany J. Heaton; Yvonne Perrie; Neill J. Liptrott (Pharmaceutics, 2022)
Lipidic nanoparticles (LNP), particularly liposomes, have been proven to be a successful and versatile platform for intracellular drug delivery for decades. Whilst primarily developed for small molecule delivery, liposomes have recently undergone a renaissance due to their success in vaccination strategies, delivering nucleic acids, in the COVID-19 pandemic. As such, liposomes are increasingly being investigated for the delivery of nucleic acids, beyond mRNA, as non-viral gene delivery vectors. Although not generally considered toxic, liposomes are increasingly shown to not be immunologically inert, which may have advantages in vaccine applications but may limit their use in other conditions where immunological responses may lead to adverse events, particularly those associated with complement activation. We sought to assess a small panel of liposomes varying in a number of physico-chemical characteristics associated with complement activation and inflammatory responses, and examine how basophil-like cells may respond to them. Basophils, as well as other cell types, are involved in the anaphylactic responses to liposomes but are difficult to isolate in sufficient numbers to conduct large scale analysis. Here, we report the use of the human KU812 cell line as a surrogate for primary basophils. Multiple phenotypic markers of activation were assessed, as well as the release of histamine and inflammasome activity within the cells. We found that larger liposomes were more likely to result in KU812 activation, and that non-PEGylated liposomes were potent stimulators of inflammasome activity (four-fold greater IL-1β secretion than untreated controls), and a lower ratio of cholesterol to lipid was also associated with greater IL-1β secretion ([Cholesterol:DSPC ratio] 1:10; 0.35 pg/mL IL-1β vs. 5:10; 0.1 pg/mL). Additionally, PEGylation appeared to be associated with direct KU812 activation. These results suggest possible mechanisms related to the consequences of complement activation that may be underpinned by basophilic cells, in addition to other immune cell types. Investigation of the mechanisms behind these responses, and their impact on use in vivo, are now warranted.